2005
DOI: 10.1007/s00520-005-0891-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of febrile neutropenia in cancer patients by probiotic strain Enterococcus faecium M-74. Phase II study

Abstract: Febrile neutropenia (FN) remains a potentially life-threatening complication of anticancer chemotherapy. Bacterial translocation via intestinal mucosa is a significant mechanism of FN development. Competitive inhibition of bowel colonization by pathogenic microorganisms by lactic acid bacteria could be a useful prevention of FN. The aim of the study was the prevention of FN by probiotic strain Enterococcus faecium M-74 enriched with selenium in leukemic patients. Fourteen (six males/eight females) patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
1
34
1
1
Order By: Relevance
“…In the study by Mego et al, administration of Enterococcus faecium M-74 enriched with selenium was started from day −2 and day+2 of chemotherapy, and colonization in the gut reached a median of 10 4 , 10 4 , <10 2 , and 10 5 CFU/g of feces at 1, 2, 3, and 4 weeks, respectively. Febrile episodes were not reported to be prevented in the study [20,21]. However, in the current study, although based on limited number of patients, administration of probiotic developed a tendency to decrease the frequency and duration of febrile episodes, which was associated with less parenteral antibiotic use.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In the study by Mego et al, administration of Enterococcus faecium M-74 enriched with selenium was started from day −2 and day+2 of chemotherapy, and colonization in the gut reached a median of 10 4 , 10 4 , <10 2 , and 10 5 CFU/g of feces at 1, 2, 3, and 4 weeks, respectively. Febrile episodes were not reported to be prevented in the study [20,21]. However, in the current study, although based on limited number of patients, administration of probiotic developed a tendency to decrease the frequency and duration of febrile episodes, which was associated with less parenteral antibiotic use.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study, the administration of probiotic strain BBG-01 did not lead to an increase in either infection or mortality, even during prolonged, severe neutropenia and demonstrated the safety of the tested probiotic strain in this patient population. However, further study involving larger number of oncologic patients is needed to draw any definitive conclusion concerning the safety of probiotic administration because so far, only a few studies have been published with each involving a limited number of oncologic patients for different probiotic strains [20,21]. The differences in the type and dose of chemotherapy between the groups are important to the study.…”
Section: Discussionmentioning
confidence: 97%
“…In vivo, data in experimental animals with cirrhosis as to the possible efficacy of probiotics in preventing bacterial translocation are conflicting, despite evidence of successful intestinal colonization, possibly related at least in part to differences in the specific bacterial strains used [145][146][147][148]. In the clinical setting, a recent pilot study has suggested that treatment with the probiotic strain Enterococcus faecium M-74 may prevent episodes of febrile neutropoenia in patients receiving anticancer chemotherapy [149]. Reported experiences as to any clinically relevant reduction in risk of SBP and other bacterial infections in patients with cirrhosis are lacking.…”
Section: Prophylaxismentioning
confidence: 95%
“…In a group of 14 leukemia patients, pretreatment before chemotherapy continuing until the resolution of severe neutropenia (absolute neutrophil count > 1,000/ll) did not prevent the development of febrile neutropenia [105]. However, no evident toxicity of the therapy was identified.…”
Section: Immune Modulationmentioning
confidence: 92%